Intracytoplasmic Sperm Injection Indications, Techniques and Applications (Springer International Publishing, 2018)
This unique, comprehensive text on the male factor infertility experience centers on the current background, applications and techniques for intracytoplasmic sperm injection (ICSI), one of the more commonly utilized procedures in modern assisted reproduction for male infertility, offering insights into the rationale and indications for ICSI and providing an up-to-date discussion on male factor diagnostic tests and microsurgical techniques for ICSI itself. Topics covered include the role of reproductive genetics, the effects of paternal age, the assessment, development and selection of functional human spermatozoa (e.g., Comet assay), both naturally and in the laboratory, and the procedures by which these sperm are injected directly into an oocyte. Comparisons are made between efficacy rates of ICSI versus conventional IVF strategies, and clinical approaches to fertilization failures following ICSI are presented, and intracytoplasmic morphologically selected sperm injection (IMSI) is discussed in detail in a chapter of its own. Bringing together the latest evidence and written by international leaders in the field, Intracytoplasmic Sperm Injection: Indications, Techniques and Applications is a unique and accessible resource for reproductive endocrinologists, andrologists, geneticists and infertility practitioners and researchers alike.